Measurement of the Effect of Chromaticity and Intensity on Colour Representation Parameters of a CRT Display - Wenzel, Klára; Urbin, Ágnes (Recent Innovations in Mechatronics, 2015)
The aim of the measurement detailed in this paper was to measure the just-noticable stimuli of the participating subjects. The stimuli were defined by chromaticity and intensity as the main parameters of the mathematical model. The results show correlance between intensity and the just-noticable stimuli, as described in the Weber-Frechner Law but a contradiction was shown after the analysis in the function of chromaticity. This contradiction can be explained by the difference between the sensitivity of the three cones of the eye.